Prospective multicenter German study on pulmonary colonization with Scedosporium /Lomentospora species in cystic fibrosis: Epidemiology and new association factors. - Carsten Schwarz; Claudia Brandt; Elisabeth Antweiler; Alexander Krannich; Doris Staab; Sabina Schmitt-Grohé; Rainald Fischer; Dominik Hartl; Anja Thronicke; Kathrin Tintelnot (PLoS ONE)
Background An increasing rate of respiratory colonization and infection in cystic fibrosis (CF) is caused by fungi of the Scedosporium apiospermum species complex or Lomentospora prolificans (Sac-Lp). These fungi rank second among the filamentous fungi colonizing the CF airways, after Aspergillus fumigatus. However, the epidemiology, clinical relevance and risk of pulmonary colonization with Sac-Lp are rarely understood in CF. The objective of the present prospective multicenter study was to study pathogen distribution and determine association factors of pulmonary Sac-Lp colonization in patients with CF. Material and methods Clinical, microbiological and laboratory data of 161 patients aged 6-59 years with CF in Germany were analyzed for Sac-Lp distribution and association factors. The free statistical software R was utilized to investigate adjusted logistic regression models for association factors. Results Of the 161 patients included in the study, 74 (56%) were male. The median age of the study cohort was 23 years (interquartile range 13-32 years). 58 patients of the total cohort (36%) were < 18 years old. Adjusted multivariate regression analysis revealed that Sac-Lp colonization was associated with younger age (OR 0.8684, 95%CI: 0.7955-0.9480, p<0.005) and less colonization with H. influenzae (OR 0.0118, 95%CI: 0.0009-0.1585, p<0.001). In addition, Sac-Lp-colonized patients had more often allergic bronchopulmonary aspergillosis (ABPA) (OR 14.6663, 95%CI: 2.1873-98.3403, p<0.01) and have been colonized more often with the mucoid phenotype of Pseudomonas aeruginosa (OR 9.8941, 95%CI: 1.0518-93.0705, p<0.05). Conclusion Newly found association of ABPA and Pseudomonas revealed new probable risk factors for Sac-Lp colonization. Allergy might play a role in inducing immunologic host reactions which lead to a less effective response to species of Sac-Lp.